The effect of work engagement, organizational commitment, and innovative behavior on employee performance - Salatun, Ria Andriatna; Rachmat, Basuki; Prawitowati, Tjahjani (Manajemen dan Bisnis, 2025)
This study aims to examine the effect of work engagement, organizational commitment, and innovative behavior on employee performance at the Public Health Centre in the North Surabaya area. This study employs a quantitative approach, collecting data through questionnaires. The research sample consisted of 186 Public Health Centre employees in the North Surabaya area who had worked as health workers for at least one year and were working at the Surabaya Health Center in the North Region at the time of the study, who were selected by purposive sampling. Data were analyzed using Structural Equation Modelling (SEM) techniques with Partial Least Square (PLS). The results showed that work engagement, organizational commitment, and innovative behavior have a significant positive effect on employee performance. This study suggests that the Public Health Centre design a strategic program to improve work engagement and organizational commitment by creating a conducive work environment, forming a solid work team, and creating an environment that supports innovative behavior to improve the performance of Public Health Centre employees. The findings provide practical implications that increasing work engagement and organizational commitment, as well as creating an environment that supports innovative behavior, will automatically improve the performance of public health service employees.